Behaviour and Quantification Studies of Venlafaxine Using Differential Pulse Stripping Voltammetric in Capsules - Qiu, Ping; Liu, Congsen; Lin, Daiqin; Zeng, Guang (Asian Journal of Chemistry, 2013)
A simple and rapid voltammetric method has been developed for the quantitative determination of venlafaxine in pharmaceutical capsules. Studies with differential pulse stripping voltammetry (DPSV) were carried out using a hanging mercury drop electrode (HMDE) in Britton-Robison buffer. A well-defined oxidation peak of venlafaxine was obtained at -432 mV vs. Ag/AgCl. The optimum working conditions for the determination of the compound were established. The detection and quantification limits were found to be 0.0993 and 0.1 μg/mL, respectively. An analysis of real samples containing venlafaxine showed no interferences with common additives and excipients. The method proposed does not require any pretreatment of the pharmaceutical capsules. A HPLC determination of venlafaxine in capsule samples diluted was also performed for comparison.